Microbiological quality and shelf-life of chilled cod fillets in vacuum-skin and modified atmosphere packaging - A. Galli; L. Franzetti; L.Piergiovanni; S. Carelli; P. Fava (Packaging Technology and Science, 1993)
The microbiological quality and shelf-life of fresh cod fillets (Gadus morhua) packed under modified atmospheres (CO2/N2/O2, 40:20:40) were compared to air and vacuum-skin packed fillets. Packed fillets were kept at 0 ± 1°C and chemical and microbiological analyses as well as sensory assessment were carried out after 4, 6 and 8 days. The decomposition process was evaluated through microbial and enzymatic proteolysis by means of total volatile nitrogen measurement, acetic acid values, surface pH and organoleptic tests. The microbiological quality was established by evaluating the growth of microbial species responsible for spoilage (total bacteria count. Gram-negative bacteria, H2S-producers) and identifying isolated species. Modified atmosphere packaging gave the best results and the high oxygen content did not affect the microbiological quality in the presence of 40% carbon dioxide. Vacuum-skin packed fillets gave less satisfactory results owing to poor chemical and microbiological indices, even if they we-e always better than fillets maintained in air.